O-Cyclic Phytosphingosine-1-Phosphate Protects against Motor Dysfunctions and Glial Cell Mediated Neuroinflammation in the Parkinson's Disease Mouse Models - Hyeon Jin Lee; Kyonghwan Choe; Jun Sung Park; Amjad Khan; Min Woo Kim; Tae Ju Park; Myeong Ok Kim (MDPI AG, 2022)
O-cyclic phytosphingosine-1-phosphate (cPS1P) is a novel and chemically synthesized sphingosine metabolite derived from phytosphingosine-1-phosphate (S1P). This study was undertaken to unveil the potential neuroprotective effects of cPS1P on two different mouse models of Parkinson's disease (PD). The study used 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and neuron specific enolase promoter human alpha-synuclein (NSE-hαSyn) Korl transgenic mice. MPTP was injected for five consecutive days and cPS1P was injected for alternate days for six weeks intraperitoneally. We performed behavioral tests and analyzed the immunohistochemistry and immunofluorescence staining in the substantia nigra pars compacta (SNpc) and the striatum. The behavior tests showed a significant reduction in the motor functions in the PD models, which was reversed with the administration of cPS1P. In addition, both PD-models showed reduced expression of the sphingosine-1-phosphate receptor 1 (S1PR1), and α-Syn which was restored with cPS1P treatment. In addition, administration of cPS1P restored dopamine-related proteins such as tyrosine hydroxylase (TH), vesicular monoamine transporter 2 (VMAT2), and dopamine transporter (DAT). Lastly, neuroinflammatory related markers such as glial fibrillary acidic protein (GFAP), ionized calcium-binding adapter protein-1 (Iba-1), c-Jun N-terminal kinases (JNK), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB), tumor necrosis factor-alpha (TNF-α), and interleukin 1 beta (IL-1β) were all reduced after cPS1P administration. The overall findings supported the notion that cPS1P protects against dopamine depletion, neuroinflammation, and PD-associated symptoms.